De novo hiatal hernia of the gastric tube after sleeve gastrectomy. (2015) - Amor, Imed Ben; Debs, Tarek; Kassir, Radwan; Anty, Rodolphe; Amor, Virginie Ben; Gugenheim, Jean
Highlights: Obesity itself is an independent risk factor for hiatal hernia. The mechanisms responsible for the development of a de novo hiatal hernia are difficult to identify. The dissection of the angle of his during creation of the gastric tube may also increase the risk of herniation. Abstract: Introduction: Sleeve gastrectomy (SG) is a frequently used surgical procedure for the treatment of morbid obesity. Several complications of SG have been described; however, de novo hiatal hernia of the gastric tube, as a complication of SG, has not been described in the literature. Presentation of case: Here, we report a case of a hiatal hernia 2 years after SG. In the case reported here, the hiatal hernia was associated with weight regain. The mechanisms responsible for the herniation of the pouch are difficult to identify. Conversion from sleeve gastrectomy to Roux-en-Y gastric bypass is an effective treatment for this complication. Its management is safe and effective. Discussion: Obesity itself is an independent risk factor for hiatal hernia, found preoperatively in more than half of the morbidly obese patients. This predisposition is explained by higher intra-gastric pressure due to intra-abdominal or visceral fat, reduced inferior oesophageal sphincter pressure, and oesophageal motility problems. Conclusion: To our knowledge, this is the first described case of hiatal hernia of the gastric tube after SG.